Hypercalcaemia, adrenal insufficiency and bilateral adrenal histoplasmosis in a middle-aged man: a diagnostic dilemma. Issue 8 (28th August 2019) - Agrawal, Sweety; Goyal, Alpesh; Agarwal, Shipra; Khadgawat, Rajesh
Abstract : A 45-year-old man presented with a 3-month history of involuntary weight loss, anorexia, postural dizziness and intermittent fever. On investigation, he was found to have parathyroid hormone (PTH)-independent hypercalcaemia, with negative workup for 25-hydroxyvitamin D or 1, 25-dihydroxyvitamin D excess, thyrotoxicosis, multiple myeloma and bony metastases. On further evaluation, he was detected to have primary hypoadrenalism with bilateral adrenal enlargement, secondary to adrenal histoplasmosis. Hypercalcaemia improved with hydration and physiological steroid replacement even before initiation of antifungal therapy, confirming adrenal insufficiency as the cause for hypercalcaemia. Hypercalcaemia resulting from hypoadrenalism secondary to adrenal histoplasmosis is rare and should be suspected whenever evaluating a patient with PTH-independent hypercalcaemia.